Design solutions of large-capacity storage tanks for liquefied natural gases - E. R. Bareeva (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The purpose of the study is to find prospects for the development of domestic large-scale isothermal LNG storage facilities to meet the required volume of export supplies from the Russian Federation.Method. During the study, modern methods of design, analysis of materials and structures were used.Result. Types of sections and joints of elements are presented. The general construction design and construction of an external reinforced concrete tank is described, taking into account the corresponding connections to the foundation and internal tank, internal tank, secondary bottom, vapor barrier, thermal protection system, domed roof, suspended ceiling, as well as the thermal insulation system of the tank. To ensure higher performance characteristics of the structure, a concrete strength class is recommended for the base slab and roofing slab and walls, as well as thermal insulation material. Requirements for the designs and materials of protective fences for large-capacity isothermal LNG storage facilities have been determined.Conclusion. The systemic relationship between all components of special building structures, building and thermal insulation materials has been determined.